2019
DOI: 10.5935/0004-2749.20190010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diameter of eyedropper tips using a computer vision system

Abstract: This study aimed to determine the variation in diameters of outer and inner apertures of eyedropper tips using a computer vision system. Standardizing the size of eye drop nozzles is crucial to reduce the treatment cost of chronic eye diseases and to ensure a continued use of medication. An eyedropper volume of >20 μL (maximum storage of the conjunctival sac) causes medication wastage and increases treatment costs. Methods: We measured the diameters of the outer and inner apertures of eyedropper tips and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The flange part of the drip chamber was machined with a lathe so that it was perpendicular to the center axis of the drip nozzle. The outer diameter and inner diameter of the tip of the drip nozzle were measured using a computer vision system PC-VJ14MEXOW (SAITOH KOUGAKU) [17]. Before the experiment, it was visually confirmed with a stereomicroscope that the lip part of the drip nozzle had no deformations or scratches.…”
Section: Drip Nozzle Used In the Experimentsmentioning
confidence: 99%
“…The flange part of the drip chamber was machined with a lathe so that it was perpendicular to the center axis of the drip nozzle. The outer diameter and inner diameter of the tip of the drip nozzle were measured using a computer vision system PC-VJ14MEXOW (SAITOH KOUGAKU) [17]. Before the experiment, it was visually confirmed with a stereomicroscope that the lip part of the drip nozzle had no deformations or scratches.…”
Section: Drip Nozzle Used In the Experimentsmentioning
confidence: 99%
“…Dropper-type infusion systems have already been the subject of several studies [13,14], which evaluated the same drug but with drippers from different manufacturing companies. They concluded that over-and under-dosing problems can occur, and suggest the standardization of drippers, as it is identified as one of the main cul-prits for the identified problems.…”
mentioning
confidence: 99%